Linking research and practice in education: the views of expert researchers in the field. Issue 2 (15th March 2023) - Anwer, Muhammad; Reiss, Michael
ABSTRACT: The existence of a gap between educational research and practice, resulting in research that makes only a limited contribution to the improvement of professional practices in education, has been a topic of much discussion. There is widespread agreement among researchers that practice in education should be informed by research evidence. At the same time, other authors have voiced concerns about giving evidence-based practice too prominent a place in educational settings. In this article, we assess the views of expert researchers in the field of education regarding the linking of research and practice in education. Individual, semi-structured interviews were undertaken with twelve experts from Pakistan and the UK, contrasting countries where the issue of the utility of research for educational practice has been much debated. In both countries, there was a strong consensus among the researchers that there are important gaps between research and practice in education. The interviewees made a range of suggestions as to how these gaps might be filled, and we examine these suggestions.